24-month results and technical approach of catheter-based renal denervation in patients with resistant hypertension. (14th October 2021) - Shugushev, Z; Chepurnoy, A; Maximkin, D
Abstract: Aim: Increase in efficiency of catheter-based renal denervation (RDN) for the treatment of resistant hypertension. Methods: 108 patients with resistant hypertension (inability to achieve target values after lifestyle changes while taking 3 antihypertensive drugs, one of which is a diuretic), were randomized in three groups. In the first two groups (n=36 in each group), RDN were performed using various devices ("Symplicity Flex", "Symplicity Spyral" and "Vessix Vascular V2"). The third control group included 36 patients who received only standardized antihypertensive therapy (AHT). The fundamental differences in procedure execution in I and II groups were as follows: 1) patients from the I group - RDN were made only of the proximal segment of the renal artery. In group II ablation performed as the proximal segment and the branches of the second and third order, where they can be safe for the patient to deliver the instrument to the electrodes; 2) the number of ablation points in the group II produced more; 3) In the group II ablation was performed in the extension of the renal arteries, while the first group of upper- and lower-pole renal artery no exposure. Inclusion criteria: patients from 18 to 85 years with refractory true systolic-diastolic hypertension I-II degrees (office SBP ≥145 mm Hg. V., DBP ≥90 mm Hg. and non-optimal drug therapy, against which the average 24-hour blood pressure monitoring of SBP ≥145 and/or <170 mm Hg); standardized triple antihypertensive therapy based at least 50% of the maximum tolerated dose for at least 6 weeks of amid lifestyle changes; appropriate renal artery anatomy for endovascular procedures. The primary endpoints: the achievement of the target SBP level (<140 mm Hg) in the first 12 months after RDN according to the results of 24-hour blood pressure monitoring. Results: Compared to the baseline blood pressure and 24 months results, the mean SBP and DBP was −5.9 mm Hg, p<0.05 and −3.8 mm Hg, p>0.05. And the maximum decrease in SBP and DBP was noted after 2 years of observation – −9.2 mm Hg, p<0.05 and −4.3 mm Hg, p<0.05, respectively. Also, there was a significant decrease in the daily average and daily average for SBP and DBP for all time of observation. In group III changes were insignificant for the first year of observation: −1.2/0.5 mmHg, p>0.05. After addition of the fourth component AHT 24 month average of SBP and DBP decreased by −4.9/1.9 mmHg, but the p value is not reached the level of less than 0.05. Conclusions: Prolonged application of radiofrequency ablation of renal artery and its branches demonstrated similar safety profile and greater efficacy of treatment of patients with resistant hypertension, compared with denervation only the main trunk of the renal artery. Improving the methods and tools for the RDN is a priority for the further development of surgical treatment of arterial hypertension resistant to optimal medical therapy. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Russian academic excellence project 5-100